Risk factors associated with recurrence of tuberculosis at the Chest Clinic, Hospital Raja Perempuan Zainab II Kota Bharu Malaysia - Myat Moe, Thwe Aung; Mainul, Haque; Mohamed Rusli, Abdullah (2015)
Introduction: Tuberculosis (TB) was the disease with the second highest incidence rate and caused the highest mortality rate among communicable diseases in Malaysia. Current study wants to identify the associated factors of recurrence among TB patients.